2021
DOI: 10.1080/08856257.2021.1961194
|View full text |Cite
|
Sign up to set email alerts
|

Social participation in the context of inclusive education: primary school students’ friendship networks from students’ and teachers’ perspectives

Abstract: Having friends influences students' academic, socio-emotional as well as health development. Especially, students with special educational needs (SEN) are at a high risk to belong to the subgroup of students without friends in class. Within a sequential explanatory design, two study phases have been implemented in the present study. In phase 1, a sociometric network analysis of 449 students from 25 inclusive primary school classes (4 th grade, age = 9-11 years) were examined at t1. To assess students' friendsh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
9
0
3
Order By: Relevance
“…Social responsibility was assessed by measuring responsibility management ( Wigmore-Álvarez et al, 2020 ), customer responsibility ( Rotjanakorn et al, 2020 ), staff responsibility ( Zhou et al, 2017 ), social services ( Lau and Li, 2018 ), and organizational responsibility ( Zhou et al, 2020 ). Similarly, institution visibility ( Tometten et al, 2021 ), environmental perception ( Hoffman et al, 2020 ), and inclusive participation ( Schwab et al, 2021 ) were evaluated by respective indicators shown in Table 1 . The questionnaire design consists of two parts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Social responsibility was assessed by measuring responsibility management ( Wigmore-Álvarez et al, 2020 ), customer responsibility ( Rotjanakorn et al, 2020 ), staff responsibility ( Zhou et al, 2017 ), social services ( Lau and Li, 2018 ), and organizational responsibility ( Zhou et al, 2020 ). Similarly, institution visibility ( Tometten et al, 2021 ), environmental perception ( Hoffman et al, 2020 ), and inclusive participation ( Schwab et al, 2021 ) were evaluated by respective indicators shown in Table 1 . The questionnaire design consists of two parts.…”
Section: Methodsmentioning
confidence: 99%
“…The kindergarten complies with national laws and regulations/legal operations Kelley et al, 2008;Merchant et al, 2012;Ivy et al, 2018;Zhou et al, 2020 The The kindergarten has a good understanding of the development and operation rules in the field of preschool education Colwell and Joshi, 2013;Ismail et al, 2014;Shafi et al, 2019;Hoffman et al, 2020;Wigmore-Álvarez et al, 2020;Schwab et al, 2021 The kindergarten is fully aware of the changes and trends in the environment and plans to respond well in advance The kindergarten can frequently communicate with peers, students, and parents to get useful information from them in time The kindergarten can detect changes in industry trends before most competitors Inclusive participation…”
Section: Responsibility Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the students in the study presented here were asked about their interactions at break time, it is not clear whether the responses were colored by the academic performance of their peers as break-time interactions do still take place in the academic context of school. On this point, Schwab et al (2021) report in their mixed-method study that children state academic performance as grounds for friendships. In turn, it is also unclear what impact friendship quality can have on other aspects such as academic performance (Sebanc et al, 2016).…”
Section: Limitationsmentioning
confidence: 99%
“…Inline, teacher's role towards inclusive education explored its theoretical and practical perspectives in different contexts – ranging from primary schools (Andrienko et al , 2017; Štemberger and Kiswarday, 2018; Schwab et al , 2021) to secondary (Paseka and Schwab, 2020; Saloviita, 2020) to higher educational institutions (Moriña, 2017; Srivastava and Shree, 2019). The studies indicated teachers as the critical asset towards effective implementation of inclusive education.…”
Section: Introductionmentioning
confidence: 99%